Attitudes, understanding and perceptions of teenagers about the use of contraceptives (Buffalo City Municipality - Eastern Cape) - Mnyanda, Phumla (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.